The Influence Of Social Media And Financial Literacy On Consumptive Attitudes In Universitas Pembangunan Panca Budi Students - Tampubolon, Sophia Valentina; Pohan, Syahrial Hasanuddin; Ananda, Geby Citra (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
In the rapidly growing digital era, social media has become an integral part of everyday life, especially for students. This study aims to determine and analyze the effect of Social Media and Financial Literacy on Consumptive Attitudes in Panca Budi Development University Students. This type of research is associative research with a quantitative approach, using a questionnaire as a data collection tool. The sample in this study consisted of 77 students of the Management Department at Universitas Pembangunan Panca Budi, which was determined using the slovin calculation. For data analysis, multiple linear regression was used with the help of SPSS version 23 software. The results of the study indicate that partially, Social Media and Financial Literacy have a significant positive influence on Consumptive Attitudes. Simultaneously, Financial Literacy and Lifestyle have a positive and significant influence on the Consumptive Attitude of Management Students at Universitas Pembangunan Panca Budi. This research model is able to explain 25%% of the variation in Consumptive Attitude.